Learning and unlearning: a context for important developments in the Seventh-day Adventist understanding of the Trinity, 1888-1898 - Valentine, Gilbert M. (Andrews University Seminary studies, 2017)
A close study of new documentary sources enables historians to know much more about the historical context for major developments in the Seventh-day Adventist understanding of the doctrine of the Trinity than what has previously been written. None of the previous studies on the development of the Trinity doctrine in Adventism seem to have considered the implications of a cluster of letters written in the 1940s in which Leroy Froom, then editor of Ministry, and Arthur Spalding, author of the Origin and History of Seventh-day Adventists, dialogued with Herbert Camden Lacey about the background to this development. As the brother-in-law to W. C. White and a retired theology teacher at the time of the exchange of correspondence, Lacey recounts a series of important theological developments in Australia in the mid-1890s. Lacey's account correlates with real-time evidence from the mid-1890s correspondence between W. W. Prescott, A. G. Daniells, E. G. White, and W. C. White, as well as with Seventh-day Adventist periodicals of the time. This article discusses this important background and its implications for the historical development of the doctrine of the Trinity in the Seventh-day Adventist Church.